A liquid larval diet for rearing Bactrocera invadens and Ceratitisfasciventris (Diptera: Tephritidae). (5th September 2014) - Ekesi, Sunday; Mohamed, Samira A.; Chang, Chiou Ling
Abstract : Bactrocera invadens Drew, Tsuruta & White and Ceratitis fasciventris (Bezzi) are the major fruit fly pests of fruits and vegetables in Africa. The effects of two types of larval diet, liquid and solid (carrot based), on various quality control parameters (pupal recovery, pupal weight, adult emergence, flight ability, fecundity and fertility) of the two fruit fly species were investigated for five generations. The potential to replace two imported ingredients (yeast and wheat germ oil) with inexpensive and locally available alternatives was also explored. Most of the quality control parameters evaluated (pupal recovery, pupal weight, adult emergence and fecundity) for B. invadens reared on a liquid diet outperformed those reared on the carrot-based solid diet. In contrast, even though C. fasciventris was able to develop successfully on the liquid diet, three of the quality control parameters evaluated (pupal recovery, pupal weight and fecundity) were significantly lower over the generations when compared with those from insects reared on a solid diet. Except for flight ability, the parameters of B. invadens reared on the diets subsituted with the local yeast were of lower quality compared with those reared on the liquid diet containing the imported yeast. Corn (maize) and soybean oils were promising substitutes for wheat germ oil in the liquid larval diet of B. invadens without compromising any of the quality control parameters.